2013
DOI: 10.1371/journal.pone.0064892
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Based Hematological and Biochemical Parameters for Macaca fascicularis

Abstract: BackgroundThe cynomolgus monkey (Macaca fascicularis) has been increasingly used in biomedical research, making knowledge of its blood-based parameters essential to support the selection of healthy subjects and its use in preclinical research. As age and sex affect these blood-based parameters, it is important to establish baseline indices for these parameters on an age and sex basis and determine the effects of age and sex on these indices.MethodsA total of 917 cynomolgus monkeys (374 males and 543 females) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
75
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 39 publications
23
75
5
Order By: Relevance
“…In this work, for both sexes, the highest ALP values were observed in the youngest animals, which were similar to those found in macaques, bonnet monkeys, marmosets, and in African green monkeys as well . This phenomenon was produced the fact that the ALP is commonly used as serum biochemical marker of bone formation and osteoblast activity .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this work, for both sexes, the highest ALP values were observed in the youngest animals, which were similar to those found in macaques, bonnet monkeys, marmosets, and in African green monkeys as well . This phenomenon was produced the fact that the ALP is commonly used as serum biochemical marker of bone formation and osteoblast activity .…”
Section: Discussionsupporting
confidence: 84%
“…In cynomolgus, Xie et al reported increase in the TP level with the increment of the animal age in both sexes. In this study, we not detected the influence of age on this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…There are various castration methods used in animals, which include physical, chemical and hormonal methods (Rajkumar, 2013).Haematological parameters are good indicators of the physiological status of animals (Khan and Zafar, 2005). Several non-genetic factors including castration affecting haematological parameters of farm animals have been observed (Svoboda et al, 2005;Xie et al, 2013). PCV, Hemoglobin concentration (Hb) and RBC were significantly reduced at 1, 2 and 3hours as compared to pre-castration level in this study.…”
Section: Discussionsupporting
confidence: 50%
“…On the one hand, it is important to take age and race/ethnicity into consideration, for example it's not suitable for using in children and adolescents [56,57]. On the other hand, several diseases or condition can influence the HbA1c value, lower HbA1c values are found in conditions such as recent transfusion and increased erythropoiesis secondary to hemolysis or blood loss, chronic kidney disease (CKD), anemia [58][59][60], to the contrary, asplenia and Iron deficiency anemia will lead a higher HbA1c values [61,62]. We also take above concerns into account, the hematology results were in normal range in adult monkeys [63].…”
Section: Discussionmentioning
confidence: 99%